2019
DOI: 10.1039/c9cp04863d
|View full text |Cite
|
Sign up to set email alerts
|

First-principles calculation of the electronic and optical properties of a new two-dimensional carbon allotrope: tetra-penta-octagonal graphene

Abstract: A novel sp2 hybridized planar 2D carbon allotrope consisting of tetra, penta and octagonal (TPO) rings is proposed in this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…The data show that when the temperature is 3000 K, the Pmc 2 1 structure undergoes large oscillations, but the chemical bonds remain stable; when the temperature reaches 3500 K, the bonds in the Pmc 2 1 structure begin to break. Therefore, the Pmc 2 1 structure can be stabilized at least to a high temperature of 3000 K, which is higher than the stable temperature of the previously proposed tetra, penta and octagonal (TPO)-graphene of about 2000 K, 41 M-graphene at about 2000 K, 42 and Be 5 C 2 at around 2000 K, 43 and slightly lower than Me-graphene at about 3500 K. 44 The MD simulations indicate that 2D Pmc 2 1 is highly thermally stable. Therefore, the phonon spectrum and AIMD simulations indicate that 2D Pmc 2 1 is highly dynamic and thermally stable.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The data show that when the temperature is 3000 K, the Pmc 2 1 structure undergoes large oscillations, but the chemical bonds remain stable; when the temperature reaches 3500 K, the bonds in the Pmc 2 1 structure begin to break. Therefore, the Pmc 2 1 structure can be stabilized at least to a high temperature of 3000 K, which is higher than the stable temperature of the previously proposed tetra, penta and octagonal (TPO)-graphene of about 2000 K, 41 M-graphene at about 2000 K, 42 and Be 5 C 2 at around 2000 K, 43 and slightly lower than Me-graphene at about 3500 K. 44 The MD simulations indicate that 2D Pmc 2 1 is highly thermally stable. Therefore, the phonon spectrum and AIMD simulations indicate that 2D Pmc 2 1 is highly dynamic and thermally stable.…”
Section: Resultsmentioning
confidence: 74%
“…In addition, the Poisson's ratio has a minimum value of about 0.19 in the 0° direction, and the maximum value of about 0.69 appeared between 30° and 60°. The Poisson's ratio of the Pmc 2 1 structure is higher than that of TPO-graphene (0.156), 41 and is different from the negative Poisson's ratio of black phosphorus (−0.027) 46 and penta-graphene (−0.068). 39…”
Section: Resultsmentioning
confidence: 84%
“…NDC refers to the behavior where the current decreases as the applied bias voltage increases. Currently, most 2D materials with NDC belong to the family of van der Waals heterojunctions. However, due to the limited interlayer tunneling efficiency for the heterojunctions, achieving a high peak current is still a challenge. However, a single 2D sheet with NDC has the potential to overcome this challenge. ,,, …”
Section: Methods For Optimizing Structures and Computing Electronic P...mentioning
confidence: 99%
“…55−58 However, a single 2D sheet with NDC has the potential to overcome this challenge. 6,22,55,59 T h i s c o n t e n t i s Recently, Zhang et al predicted that 2D monolayer (ML) and bilayer (BL) tetrahex-GeC 2 would exhibit high-anisotropic mobility and thermodynamic stability. 60 The ML tetrahex-GeC 2 has been suggested to possess a direct band gap of 0.89 eV, which is 0.26 eV less than the band gap of bulk silicon, and an electron mobility of 9.5 × 10 4 cm 2 /V/s.…”
mentioning
confidence: 99%
“…In recent years, people found many 2D materials from allotropes of carbon and from group V elements. Some of them have potential application in optoelectronic, nano electronic devices and hydrogen storage, because of their unique electronic and mechanical properties [4][5][6][7][8][9][10]. In 2018, Cao et al found the twisted bilayer graphene is able to be an insulator or superconductor [11,12].…”
Section: Introductionmentioning
confidence: 99%